Chinese version and application of the global health competencies survey for healthcare professionals - Li, Xiaoxi; Jia, Junjie; Hu, Jingjing; He, Xuqi; Zheng, Meiqiong (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to introduce and validate the global health competencies survey (GHCS) in the Chinese healthcare context, addressing the need for a comprehensive tool to assess global health competencies among diverse healthcare professionals.MethodsThe GHCS underwent meticulous translation and cultural adaptation, engaging 150 healthcare professionals from various disciplines between 1st June and 10th December, 2023. The study employed a rigorous methodology involving instrument development, translation, data collection, and statistical analysis. Face and content validity, factor analysis, and internal consistency were assessed to validate the survey.ResultsThe translated GHCS demonstrated robust reliability (Cronbach’s alpha = 0.841) and validity. The survey identified competencies, showcased temporal trends, and informed targeted interventions. No floor or ceiling effects were observed, except for one variable (racial/ethnic disparities).ConclusionThe adapted and validated GHCS emerges as a valuable tool for assessing global health competencies among Chinese healthcare professionals. Implications for research use include identifying knowledge gaps, facilitating program improvements, and contributing to reduced health inequities. Despite limitations, such as the absence of criterion validation and Mandarin administration, the GHCS offers a foundation for further research and program enhancements in China.